2014
DOI: 10.1126/scitranslmed.3006763
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p21Rac Signaling and Increased Innate Immunity Mediate Remission in Crohn’s Disease

Abstract: In inflammatory bowel disease (IBD), large areas of apparently healthy mucosa lie adjacent to ulcerated intestine. Knowledge of the mechanisms that maintain remission in an otherwise inflamed intestine could provide important clues to the pathogenesis of this disease and provide rationale for clinical treatment strategies. We used kinome profiling to generate comprehensive descriptions of signal transduction pathways in inflamed and noninflamed colonic mucosa in a cohort of IBD patients, and compared the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…The effect appeared to be TGN dependent (or a related metabolite) dependent because this effect was abolished in Hprt −/− fibroblasts (figure 6). These data—the TG-enhanced bactericidal function, the effect of TG on leucocyte subsets and the improvement in RaW murine colitis with TG—are consistent with the recent report which showed that RAC1 inhibition could boost innate immunity 47. Thus, compared with the slow pharmacodynamics action effected by loading of circulating effector lymphocytes, TG treatment of IBD could occur more rapidly through the local conversion of TG to thioGTP by mucosal or microbial HPRT.…”
Section: Discussionsupporting
confidence: 90%
“…The effect appeared to be TGN dependent (or a related metabolite) dependent because this effect was abolished in Hprt −/− fibroblasts (figure 6). These data—the TG-enhanced bactericidal function, the effect of TG on leucocyte subsets and the improvement in RaW murine colitis with TG—are consistent with the recent report which showed that RAC1 inhibition could boost innate immunity 47. Thus, compared with the slow pharmacodynamics action effected by loading of circulating effector lymphocytes, TG treatment of IBD could occur more rapidly through the local conversion of TG to thioGTP by mucosal or microbial HPRT.…”
Section: Discussionsupporting
confidence: 90%
“…The peptide array data analysis was done as described earlier (Parikh et al, 2014). ScanAlyze software was used.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-TNFα therapy, a well known and highly effective treatment for IBD, may suppress the activation of Rac1–GTP similar to thiopurine therapy which may contribute to the immunosuppressive effect of anti-TNFα therapy [55]. The SONIC (Study of Biologic and Immunomodulator Naive Patients in Crohn’s Disease) and SUCCESS (Efficacy & Safety of Infliximab Monotherapy vs Combination Therapy vs AZA Monotherapy in Ulcerative Colitis) trials have shown that, in IBD patients, combination therapy consisting of anti-TNFα and thiopurine therapy is more effective than monotherapy with either anti-TNFα or azathioprine [56, 57].…”
Section: Modulation Of the Rac Pathways By Thiopurine Therapymentioning
confidence: 99%